The Leisure Society - Porter, Gerry (2008)
Colour Brad Hodder (director), Brian Bishop (lighting design), Shannon Hawes (sound design). Featuring Petrina Bromley, Aiden Flynn, Jessica Power, Jonathan Watton C2C Theatre